185 BETA-BLOCKERS OR CALCIUM CHANNEL BLOCKERS IN HYPERTROPHIC CARDIOMYOPATHY. (15th December 2022) - Pinto, Giuseppe; Chiarito, Mauro; Bacher, Anne; Puscas, Tania; Condorelli, Gianluigi; Reant, Patricia; Donal, Erwan; Hagege, Albert
Abstract: Background: Guidelines recommend betablockers (BB) as first line therapy in symptomatic patients with hypertrophic cardiomyopathy (HCM). A secondary role in the therapeutic algorithm is assigned to non-dihydropyridine calcium channel blockers (ND-CCB). Since no randomized comparison trials between the two drugs have been made so far, the aim of the present analysis was to evaluate the prognostic impact of BB and ND-CCB in a cohort of patients with HCM, either obstructive or not. Methods: From a cohort of 1434 patients with a diagnosis of HCM included in the French register REMY, we retrospectively analysed 601 individuals treated with BB or ND-CCB. Patients taking both BB and ND-CCB or none, patients who already had an implantable cardioverter defibrillator or a pacemaker and who had already undergone a procedure of atrial fibrillation (AF) ablation or of septal reduction therapy were excluded. Results: Out of 601 HCM patients, 545 (91%) were treated with BB and 56 (9%) with ND-CCB. At 8-year follow-up no differences were observed as regard the composite endpoint of cardiovascular death, hospitalization for heart failure and hospitalization for AF (133 [24%] vs. 9 [16%] for patients taking BB or ND-CCB respectively, HR 1.84, 95% CI 0.94–3.63). Patients taking ND-CCB were less symptomatic at long-term follow-up but experienced more drug interruptions or changes. Conclusions: In a real-world cohort of patients with HCM, ND-CCB therapy was not associated with a higher incidence of adverse events compared to BB therapy.